Clinical and Functional Differences Between Mexican Youth at Clinical High Risk for Psychosis and With Familial High Risk - Nieto, Lourdes; Domínguez-Martínez, Tecelli; Rosel-Vales, Mauricio; Saracco-Alvarez, Ricardo; Celada-Borja, Cesar; Rascón-Gasca, María Luisa (Frontiers in Psychology, 2022)
Few studies have explored the differences in clinical psychopathology between youth at high risk for psychosis and those at familial high risk for psychosis. This study seeks to describe and compare the sociodemographic, clinical, and functional characteristics of At-Risk Mental State (ARMS) for psychosis youth and those with a first- or second-degree relative with psychosis (Familial High-Risk: FHR) in a Mexican sample. Twenty-one ARMS individuals and 21 with FHR were evaluated for sociodemographic characteristics, psychopathological symptoms, and functional impairment. ARMS individuals were significantly younger, had fewer years of schooling, and were more likely to be male than those in the FHR group. Groups did not differ as regards marital status or occupation. The ARMS group showed greater severity of prodromal symptoms, schizotypal personality traits, and general psychopathology than the FHR group. In addition, they reported more premorbid adjustment deficit from early adolescence than the FHR group. Current overall social and role functioning was significantly lower in the ARMS group. Findings are consistent with ARMS studies from other countries. First- or second-degree relatives of patients with psychosis should be considered a vulnerable group as they display several symptoms of general psychopathology and may experience social adjustment problems in their adult lives. The lack of early detection and intervention psychosis programs in Mexico underlines the need to prioritize the development of preventive strategies to help close the care gap.